On a method of asymptotic expansions for infinite dimensional integrals with respect to smooth measures - Steblovskaya, V. (Methods of Functional Analysis and Topology, 2025)
We introduce a method allowing one to obtain asymptotic expansions for integrals with respect to smooth measures depending on a large parameter in infinite dimensions in the case when the phase function has a special form related to the logarithmic gradient of the measure. A number of examples is considered in details.